Understanding the Sport Participation Environment: Squash in New South Wales - Pryor, Brooke (Auckland University of Technology, 2022)
The promotion of all types of physical activity is becoming more prominent in health policy. Yet, sport participation offers additional benefits that go beyond just the physical health benefits, such as better physical role functioning, vitality, social functioning, mental health, and life satisfaction, when compared to participants of purely physical activity. Sport participation in Australia has seen a significant decline across all sports, with squash witnessing a disproportionately higher decline than others. Research on the key factors that influence sport participation is important to enable policy makers and sport managers to implement initiatives that best promote, and support, community sport participation. The context of this research is to explore the decline of squash participation in New South Wales (NSW) using the broad lens of the Socio-Ecological Model (SEM) to guide the research. The SEM highlights the key factors that influence sport participation, such as policy, environmental, organisational, interpersonal, and intrapersonal factors. The purpose of this study was to firstly, identify the key factors that have influenced squash participation in NSW and secondly, investigate potential opportunities that could address factors that have contributed to a decline of participation. A qualitative methodology using mixed methods was used to collect data. The core interview data was collected through semi-structured interviews from seven participants, and the themes that were identified from this data guided the secondary document analysis. Using thematic analysis, an understanding of the key themes that have influences squash participation and how they could be addressed to increase participation was identified. The four key themes that were identified were: facilities, development programs and pathways offered, governance, and trust between key stakeholders. Opportunities for change were then discussed relating to each of the themes. Each of the themes, and sub-themes, interacted with various levels of the SEM. Overall, this approach has generated a unique perspective of the wider environment that has influenced squash participation in NSW.